Comment on Novozhilova et al. More Capable, Less Benevolent: Trust Perceptions of AI Systems across Societal Contexts. Mach. Learn. Knowl. Extr. 2024, 6, 342–366 - Damasevicius, Robertas (Machine learning and knowledge extraction, 2024)
The referenced article [...]